2016
DOI: 10.1016/j.gca.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-group element abundances and Re–Os isotopic systematics of the upper continental crust through time: Evidence from glacial diamictites

Abstract: The fine-grained matrix of glacial diamictites, deposited periodically by continental ice sheets over much of Earth history, provides insights into the average composition and chemical evolution of the upper continental crust (UCC) , and references therein). The concentrations of platinum-group elements (PGEs, including Os, Ir, Ru, Pt and Pd) and the geochemically related Re, as well as 187 Re/ 188 Os and 187 Os/ 188 Os ratios, are reported here for globally-distributed glacial diamictites that were deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 61 publications
2
32
0
Order By: Relevance
“…Further, Garçon et al (2017) examined the 143 Nd/ 144 Nd and 176 Hf/ 177 Hf isotopic compositions of Archean metasedimentary rocks from the Barberton area, southern Africa. Consistent with the conclusions of Gaschnig et al (2016) and Chen et al (2016), that study also concluded that the Archean UCC sampled by the metasedimentary rocks was more mafic than modern UCC.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Further, Garçon et al (2017) examined the 143 Nd/ 144 Nd and 176 Hf/ 177 Hf isotopic compositions of Archean metasedimentary rocks from the Barberton area, southern Africa. Consistent with the conclusions of Gaschnig et al (2016) and Chen et al (2016), that study also concluded that the Archean UCC sampled by the metasedimentary rocks was more mafic than modern UCC.…”
Section: Introductionsupporting
confidence: 76%
“…The diamictite composites can, therefore, be considered representative of the glacially sampled UCC at each location at the time of deposition. Additional details regarding the preparation of the diamictite composites, major and trace element compositions, as well as highly siderophile element (HSE) abundances and Li, O, Ba and Re-Os isotopic compositions of individual diamictites, as well as the composites were previously reported (Gaschnig et al, 2014(Gaschnig et al, , 2016Li et al, 2016;Chen et al, 2016;Nan et al, 2018).…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixture of concentrated HCl and HNO 3 (aqua regia or reverse aqua regia) is widely used to digest geological silicate samples in high-pressure asher or Carius tubes for determination of PGE and Re mass fractions (e.g., Shinotsuka and Suzuki 2007, Fischer-G€ Li et al 2014, 2015a, Puchtel et al 2014, Chu et al 2015, Chen et al 2016, Liu et al 2016, Meisel and Horan 2016. We digested samples using reverse aqua regia in Carius tubes, and the results for Au, Re and PGEs are listed in Table 3 and Table S1.…”
Section: The Validity Of Aqua Regia Digestion For Gold Determinationmentioning
confidence: 99%